Adaptasi Burung Papua Vogelkop Superb Bird-of-Paradise dan Mambruk Victoria sebagai Sumber Ide Tata Rias Fantasi - Khofifah Alaviyah; Taofan Ali Achmadi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Indonesia's biodiversity, particularly endemic birds from Papua, possesses high aesthetic potential as a source of inspiration in the development of artistic works, including fantasy makeup. This study aims to develop a fantasy makeup design based on the visual adaptation of the Vogelkop Superb Bird-of-Paradise and the Mambruk Victoria. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The product developed was a fantasy makeup design that adapted the birds’ visual characteristics, including colors, textures, crown shapes, and feather patterns into facial makeup, body painting, headpieces, and costumes. The results showed that the product achieved a very good quality level with a percentage score of 93.68%. The instrument validity obtained an Aiken’s V value of 0.86, while the reliability test showed a Cronbach’s Alpha value of 0.988, indicating that the instrument was highly valid and reliable. This study demonstrates that visual adaptation of fauna can serve as an effective source of inspiration in developing innovative, aesthetic, and locally inspired fantasy makeup designs.